2002
DOI: 10.1002/art.10631
|View full text |Cite
|
Sign up to set email alerts
|

Timing of total joint replacement affects clinical outcomes among patients with osteoarthritis of the hip or knee

Abstract: Objective. To determine the predictors of outcome in patients with osteoarthritis 2 years after receiving total hip or knee replacement.Methods. A prospective cohort study of 222 osteoarthritis patients undergoing total hip or knee replacement in Boston and Montreal was done. Their postoperative outcomes at 6 months were previously reported. This followup reports on the outcomes after 2 years among the 165 patients (74%) who remained. The subjects were divided into 2 groups according to the median value of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
271
9
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 382 publications
(310 citation statements)
references
References 4 publications
20
271
9
10
Order By: Relevance
“…Documentation of the status of patients on waiting lists is an important clinical issue because previous research has shown that high preoperative pain and poor physical function predict poor surgical outcomes up to 2 years following total hip or knee replacement (5,9).…”
Section: Introductionmentioning
confidence: 99%
“…Documentation of the status of patients on waiting lists is an important clinical issue because previous research has shown that high preoperative pain and poor physical function predict poor surgical outcomes up to 2 years following total hip or knee replacement (5,9).…”
Section: Introductionmentioning
confidence: 99%
“…A wait time exceeding 12 months from consultation to surgery may adversely affect the 12-month outcomes after THA [13,14,24]. Based on our results, long wait times are not free from adverse effects and have irreversible effects on the results of the therapeutic intervention.…”
Section: Discussionmentioning
confidence: 71%
“…We found several factors related to quality of life that decreased when adjusted by other related variables, resulting in the ultimate determination of the waiting time: the degree of pain and function. Pain and function are crucial criteria in the prioritization process for THA [13]. As previously reported [17,22], the prioritization process should be based on broader criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations